2023
DOI: 10.1186/s12888-023-05021-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 and psychological risk factors on non-suicidal self-injury behavior among high school students: a one-year follow-up study

Abstract: Objectives Non-suicidal self-injury (NSSI) behavior is a severe public health issue in adolescents. This study investigated the possible impact of the coronavirus disease 2019 (COVID-19) and analyzed psychological risk factors on adolescent NSSI. Methods A one-year follow-up study was conducted in September 2019 (Time 1) and September 2020 (Time 2) among 3588 high school students. The completed follow-up participants (N = 2527) were classified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 99 publications
2
3
0
Order By: Relevance
“…Consistent with our hypothesis, the LS of Chinese junior high school students showed an overall downward trend from grades 7 to 9. This result is also supported by previous studies (Li & Bian, 2016; Orben et al, 2022; Wang & Zhang, 2012). The reasons for this phenomenon are as follows.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our hypothesis, the LS of Chinese junior high school students showed an overall downward trend from grades 7 to 9. This result is also supported by previous studies (Li & Bian, 2016; Orben et al, 2022; Wang & Zhang, 2012). The reasons for this phenomenon are as follows.…”
Section: Discussionsupporting
confidence: 91%
“…For example, a review of relevant studies suggests that Western teenagers' LS tends to decline slightly (Proctor et al, 2009). This finding is similarly supported by most Chinese research: LS among junior high school students generally declines from the first to the third year of junior high school (Li & Bian, 2016; Wang & Zhang, 2012). However, the current research is slightly different in the specific trajectory of change.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Balasankar Ganesan, School of Allied Health and Human Services, IHM, Australia present, NSSI is listed as an independent diagnosis in the third part of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (3). Previous studies have shown that the detection rate of NSSI in Chinese adolescents is generally higher than what is seen in Western countries (4) and is showing a gradually increasing trend (5). NSSI not only causes physical damage to adolescents, but also greatly harms their psychology, including increasing the likelihood of certain diseases, various psychological and behavioral disorders, and even suicidal behavior (6,7).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…Indeed, it has become a social public-health problem affecting the mental health of adolescents. 4 At present, the treatment of NSSI behavior in China and abroad is primarily psychotherapy. The most common is cognitive behavioral therapy, which aims to alleviate adverse emotions by improving cognition, but it often only has short-term efficacy.…”
Section: Introductionmentioning
confidence: 99%